(3cJGH GdeNJGQs - (3Ydj Hf CMeO Hf Ydj Hf YHO GdefYe, CHh GdMSf, GdegPH, GdeYQha HGHf gHd,J (B610 (3g` s
(3ChdgG (B:s
(3aUd ai CeQGV GdOeGZ hChdkG ai GdUOGY GdOeGZ eY JMUfg hYdb ecGfg s
(3BNQgG (B:s
(3bGd GdRcGe hGdYWGS ai LejY GdYdd GdJi Jchf ai GdQFI hGdCVdGY agi OdGFd QOjI hGdMeO ddg s
(3HBNQgG JQLeI ddeDdas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B21s
Keywords: (3GdWHs